Reference pricing and cost-sharing: Theory and evidence on German off-patent drugs - Annika Herr; Torben Stühmeier; Tobias Wenzel (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
This paper evaluates the impact of reference pricing on prices and co-payments in the (German) market for off-patent pharmaceuticals. We present a theoretical model with price-sensitive and loyal consumers that shows that a decrease in the reference price affects the consumers' co-payments in a non-monotonic way: For high reference prices, a marginally lower reference price may lead to lower co-payments. However, for low reference prices a further reduction may result into higher consumer co-payments. We use quarterly data on reference priced drugs covered by the social health insurance in Germany over the period 2007 - 2010 to analyze the empirical effects of reference price reductions. We find that, while prices decrease due to the reduction, co-payments behave non-monotonically and indeed increase if the reference price is sufficiently low.
Keywords: I18; I11; L13; 330